Hungarian Monitoring, 9 November 1989 . [Magyar rádiófigyelő], 1989. november 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Events in the GDR - Kohl in Warsaw - Czechoslovak CP insists on its leading role Domestic Affairs: - National Council of Trade Unions (SZOT) in the process of being dissolved - Presidential election campaign - Spanish premier's Budapest visit - Iron Curtain dismantled Economy: - Hungarian-Spanish economic relations - Prague conference on Comecon reforms - Chamber of Commerce's summary Külpolitika: - NDK események - Kohl Varsóban - A CSKP ragaszkodik vezető szerepéhez Belpolitika: - Megszűnő félben a SZOT - Elnökválasztási kampányolás - A spanyol kormányfő budapesti látogatása - Lebontották a vasfüggönyt Gazdaság: - Magyar-spanyol gazdasági kapcsolatok - Prágai tanácskozás a KGST reformjáról - A Gazdasági Kamara beszámolója